Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)2X*3X+4=104976
2x*3x*81=104976
(2*3)x=104976/81
6x=1296=64
=>x=4
b)hình như đề sai
a) ( x+1)2 =25
Ta có :
52=25
=> ( x+1)2)=52
=> x+1=5
=> x=4
b) 32x=210
=> 32x=(22.5)
=> 32x=(25)2
=> 32x=322
=> x=2
c) 9x=81
Ta có :
92=81
=> 9x=92
=> x=2
d) 3. (2x +1)2=48
=> (2x +1)2=42:3
=> (2x +1)2=16
Mà :
42=16
=> (2x +1)2=42
=> 2x+1=4
=> 2x=3
=> x=1,5
e) (x-1)4 = (x-1)2
TH1: (x-1)4 = (x-1)2=0
=> x=1
TH2: (x-1)4 = (x-1)2=1
=> x=2
Xong :)
a) \(\left(x+1\right)^2=25\)
\(\left(x+1\right)^2=5^2=\left(-5\right)^2\)
- Nếu \(x+1=5\)
\(\Rightarrow x=5-1=4\)
- Nếu \(x+1=-5\)
\(x=\left(-5\right)-1=-6\)
\(3^2.\left(x+4\right)-5^2=5.2^2\)
= \(9.\left(x+4\right)-25=5.4\)
= \(9.\left(x+4\right)-25=20\)
= \(9.\left(x+4\right)=20+25\)
= \(9.\left(x+4\right)=45\)
\(\left(x+4\right)=45:9\)
\(x+4=5\)
\(x=5-4\)
\(x=1\)
32.(x+4)-52=5.22
32.(x+4)=52+(5.22)
32.(x+4)=45
x+4=45:32
x+4=5
x=5-4
x=1
a, 3.(x-9)+15=12+243:32
3x-27+15=12+243:9
3x-12=12+27
3x=12+12+27
3x=51
x=17
b, (3x-48).6=33.22+32.23-122
18x-288=32.3.22+32.22.2-(3.2.2)2
18x-288=32.3.22+32.22.2-32.22.22
18x-288= 32.22.(3+2-22)
18x-288= 9.4.(3+2-4)
18x-288=36.1
18x-288=36
18x=36+288
18x=324
x=18
2x + 2 - 2x = 48
=> 2x . 22 - 2x = 48
=> 2x (22 - 1) = 48
=> 2x . 3 = 48
=> 2x = 16
=> 2x = 24
=> x = 4
\(2^{x+2}-2^x=48\)
\(2^x.2^2-2^x=48\)
\(2^x.\left(2^2-1\right)=48\)
\(2^x.3=48\Leftrightarrow2^x=16\)
\(2^x=16=2^4\)
Vậy x = 4